Aerial phytomass in sandy grasslands of the Province of Pampa in different classes of range condition (Semiárida, 2020)
This work tries to determine the range condition of sevel sandy grasslands of the Province of La Pampa. Fourteen different areas were chosen and standing crop during 1981 was analyzed, (this basis There were scored and classified according to the ditional range condition classes: Excelent, Good, Fair, Poor and Very Poor.